A single infusion of intravenous lidocaine for primary headaches and trigeminal neuralgia: a retrospective analysis - Mullins, C. F.; Fuccaro, M.; Pang, D.; Min, L.; Andreou, A. P.; Lambru, G. (Frontiers in Neurology, 2023)
Intravenous (IV) lidocaine has been used as a transitional treatment in headache and facial pain conditions, typically as an inpatient infusion over several days, which is costly and may increase the risk of adverse effects. Here we report on our experience using a single one-hour IV lidocaine infusion in an outpatient day-case setting for the management of refractory primary headache disorders with facial pain and trigeminal neuralgia. Methods This is a retrospective, single-centre analysis on patients with medically refractory headache with facial pain and trigeminal neuralgia who were treated with IV lidocaine between March 2018 and July 2022. Lidocaine 5 mg.kg -1 in 60 ml saline was administered over 1 hour, followed by an observation period of 30 minutes. Patients were considered responders if they reported reduction in pain intensity and/or headache frequency of 50% or greater. Duration of response was defined as short-term (<2 weeks), medium-term (2-4 weeks) and long-term (>4 weeks).Forty infusions were administered to 15 patients with trigeminal autonomic cephalalgias (n=9), chronic migraine (n=3) and trigeminal neuralgia (n=3). Twelve patients were considered responders (80%), eight of whom were complete responders (100% pain freedom). The average duration of the treatment effect for each participant was 9.5 weeks (range 1-22 weeks). Six out of 15 patients reported mild and self-limiting side effects (40%).A single infusion of IV lidocaine might be an effective and safe transitional treatment in refractory headache conditions with facial pain and trigeminal neuralgia. The sustained effect of repeated treatment cycles in some patients may suggest a role as long-term preventive therapy in some patients.